Regulatory role of lnc-MAP3K13-3:1 on miR-6894-3p and SHROOM2 in modulating cellular dynamics in hepatocellular carcinoma - Kuai Chen; Manqin Zhu; Qinghua Hu; Hui Huang; Ka Chen; Xia Shuai; Jinshi Huang; Qiang Tao; Zhibin Guo (BMC Cancer)
Abstract Background Hepatocellular carcinoma (HCC) is a prevalent primary liver malignancy and a leading cause of cancer-related mortality worldwide. Despite advancements in therapeutic strategies, the 5-year survival rate for individuals undergoing curative resection remains between 10% and 15%. Consequently, identifying molecular targets that specifically inhibit the proliferation and metastasis of HCC cells is critical for improving treatment outcomes. Database analysis using Targetscan identified complementary binding sites for the human-specific miRNA hsa-miR-6894-3p (hereafter referred to as miR-6894-3p) on SHROOM2, and Starbase data suggested a potential regulatory interaction between lnc-MAP3K13-3:1 and miR-6894-3p in liver cancer. Objective This study aimed to investigate the role of lnc-MAP3K13-3:1 in regulating miR-6894-3p, with a focus on its impact on proliferation, apoptosis, migration, and related cellular processes in liver cancer cells via SHROOM2 regulation. Methods Quantitative PCR (qPCR) was initially employed to measure the expression levels of lnc-MAP3K13-3:1 and miR-6894-3p in three HCC cell lines: HepG2, HuH-7, and Li-7. Based on these initial assessments, two cell lines were selected for further experimentation. Stable cell lines overexpressing lnc-MAP3K13-3:1 were developed, and cells were transfected with miR-6894-3p mimics or a mimic negative control (NC). After 24 h, qPCR was utilized to quantify the relative expression of lnc-MAP3K13-3:1, miR-6894-3p, SHROOM2, and Caspase9 mRNA in each group. Cell proliferation was analyzed using the cell counting Kit-8 assay, while flow cytometry was used to assess cell cycle distribution and apoptosis. Migration capabilities were evaluated through cell scratch assays, and dual-luciferase assays were utilized to verify interactions between miR-6894-3p, lnc-MAP3K13-3:1, and SHROOM2. Results Overexpression of lnc-MAP3K13-3:1 and miR-6894-3p mimic transfection resulted in increased expression of SHROOM2 and Caspase9 mRNA, as demonstrated by qPCR. The miR-6894-3p mimic regulated the activity of lnc-MAP3K13-3:1. Functional assays showed that lnc-MAP3K13-3:1 overexpression inhibited proliferation in HuH-7 and Li-7 cells, promoted apoptosis, reduced migration in Li-7 cells, but enhanced migration in HuH-7 cells. Additionally, lnc-MAP3K13-3:1 overexpression significantly increased the proportion of HuH-7 cells in the G2/M phase and Li-7 cells in the S phase. The miR-6894-3p mimic modulated the effects of lnc-MAP3K13-3:1 on cell proliferation, apoptosis, and migration. Dual-luciferase assays confirmed direct binding between lnc-MAP3K13-3:1 and miR-6894-3p, as well as between miR-6894-3p and SHROOM2. Conclusion These findings indicate that overexpression of lnc-MAP3K13-3:1 regulates SHROOM2 expression through targeting miR-6894-3p, thereby influencing cell proliferation, apoptosis, migration, and other cellular processes associated with HCC.